Changes In Logistics Services in The Transition to The Digital Economy - Xiaohui Zhou; Tatiana Samuseva (Communications of International Proceedings, 2021)
Based on an assessment of the structure and dynamics of development of the current position of logistics services in the international market, caused by the pandemic, the authors in this article try to substantiate the ongoing processes that contribute to an increase in the efficiency of the industry. The author highlights important development trends that are associated with the functioning of the logistics services industry in the international market, as well as the development of the logistics industry due to digitalization.
Keywords: world market; international trade in services; logistics services market; logistics; transport and logistics services; global logistics services market.